APLIKASI MANAJEMEN BIRO WISATA & TRAVEL BERBASIS JAVA PADA PT GLOBAL SERVICE WISATA - Aji Putro Prasetyo; Ahmad Fauzi; Andi Dwi Pangestu (CV. Denasya Smart Publisher, 2024)
The purpose of this research is to design and create a travel agency management application system. This is done by changing the manual system by replacing it with a desktop-based application system whose data management and processing is stored with a database system. The development method used in this research is the SDLC (System Development Life Cycle) system. SDLC System Development Method The SDLC method is a method in which the system development and design process goes through several stages, from system planning to operation and maintenance. Data collection methods used in this study were: observation, interviews, and literature study. This research produces an application that can help tourists in traveling.